Is the Sublingual Artery a Reliable Alternative for Intraoral Anastomoses in Head and Neck Free-Flap Reconstruction? Anatomical Basis and Preliminary Results - Vasco Starke; Jürgen Wallner; Robert Stigler; Sidney Mannschatz; Jakob Müller; Erich Brenner (Journal of Vascular Diseases, 2024)
Background/Objectives: Head and neck free-flap reconstructions are often required to treat tumors or extensive post-traumatic jaw defects. The facial artery is the standard receiving vessel for intraoral microvascular anastomoses. However, its use is associated with several disadvantages, such as lesions of buccal nerve branches of the facial nerve or the parotid duct, as well as variability in course and diameter. The aim of this study is to investigate whether branches of the sublingual artery can be considered as an alternative intraoral supply vessel to the facial artery to avoid these drawbacks. Methods: Twelve formalin-fixed cadaveric heads with 24 sides (n = 24) were dissected. The origin, course, branching pattern, and distribution of the sublingual artery were examined. In addition, the diameters of the branches of the sublingual artery were assessed to identify potential supply vessels for anastomoses. Results: In ten of the twenty-four cases (41.7%), the sublingual artery originated from the lingual artery, and in nine cases (37.5%), the lingual artery originated from the facial artery. The main trunk of the sublingual artery was present in the floor of the mouth in all cases (100%), with a diameter of ≥0.9 mm in vitro (1 mm in vivo). In 15 of the 24 half heads (62.5%), branches of the sublingual artery with ≥0.9 mm were identified in this space, with the main branch being considerably stronger. Conclusions: The large diameter of the sublingual artery in the floor of the mandible suggests that this vessel or its branches could be considered as alternative pedicles for intraoral anastomoses in mandibular microvascular free-flap grafts.